Diagoras of Melos: a contribution to the history of ancient atheism - Winiarczyk, Marek (Beiträge zur Altertumskunde, 2016)
Diagoras of Melos (lyric poet, 5th c. B.C.) has received special attention for some time now because he was regarded as a radical atheist and the author of a prose work on atheism in antiquity. He was notorious for revealing and ridiculing the Eleusinian Mysteries and was condemned for impiety at Athens. The present book evaluates Diagoras’ biography and shows that he cannot be considered to have been an atheist in the modern sense.